Characterization of photo-oxidative degradation process of polyolefins containing oxo-biodegradable additives. (2nd December 2022) - Padermshoke, Adchara; Kajiwara, Tomoko; An, Yingjun; Takigawa, Mamiko; Van Nguyen, Toan; Masunaga, Hiroyasu; Kobayashi, Yutaka; Ito, Hiroshi; Sasaki, Sono; Takahara, Atsushi
Abstract: The effects of oxo-biodegradable additives on the photo-oxidation of four types of polyolefin polymers, namely high-density polyethylene (HDPE), low-density PE (LDPE), linear low-density PE (LLDPE), and isotactic polypropylene ( it PP) were investigated. Scanning electron microscopy, infrared spectroscopy, differential scanning calorimetry, and wide- and small-angle X-ray scattering were employed to gain insights into the chemical and structural modifications induced by the degradation process. The photo-oxidation preferentially occurred at the sample surface and was favored in the amorphous region of the polymers. The carbonyl index calculated for the neat and additive-containing samples suggested that the additives promoted the photo-oxidative degradation, particularly of the PE polymers, which are intrinsically resistant to oxidation, without altering their degradation pathways. The overall degradation rate of the additive-containing polymers was in the order of it PP > LDPE > LLDPE > HDPE. Graphical abstract: Image 1 Highlights: Oxo-biodegradable additives promoted oxidative degradation during UV irradiation in air. Photo oxidative degradation preferentially occurred at surface and amorphous region. Photo oxidative degradation rate was in the order of it PP > LDPE = LLDPE > HDPE.